Peningkatan Indeks Pembangunan Manusia (IPM) Melalui Pendekatan Pendidikan Responsif Gender di Kabupaten Sumenep - Mansur, AH; Rahman, Mufiqur; Tang, Muhammad (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
This article aims to discuss increasing the human development index through a gender-responsive education approach. This article uses a library research approach with content analysis techniques. The results showed that the HDI of Sumenep Regency was still relatively low, namely that males were at 72.32% while females were at 58.38%. This figure illustrates that there are still significant differences between males and females. One of the indicators is the school average of 6.60% for boys and 4.63% for girls. This fact is still detrimental to women. Then the Gender Empowerment Index (IDG) in Sumenep is 60.99% better than other districts in Madura. IDG Sumenep data from 2010 to 2019 shows a fairly good increase, even better than other districts in Madura. However, this gap is still a development problem in the field of education in Sumenep. This study shows the revitalization of the human development agenda in the field of gender responsive education, especially in rural areas and islands. Development challenges in Sumenep are still faced with cultural praxis, some of which are not yet in favor of gender equality. The Sumenep government should be able to increase the human development index through gender responsive education, by making this study a recommendation to the relevant agencies. One of them is revitalizing the role of the education board, by optimizing the function of the education board as an advisory agency, supporting agency, controlling agency, and mediating agency